Forced labor practices of Indonesian migrant fishing vessels crew on Taiwan-Flagged Ships? A need for cognitive framework transformation - Fitri Soulina; Nadia Yovani (Journal of Social Studies (JSS), 2020)
The foreign labor market delivers Indonesian workers with low qualifications for work in the informal fisheries sector as a fishing vessel crew (AKP). On the one hand, the use of Indonesian workers assists in increasing the absorption of domestic labor. Still, in real conditions, the workers are confronted with violations practices of labor rights. More than that, in the homestead, migrants' fishing vessel crew experience the repudiation of labor rights and human rights. Based on previous studies mapping, the phenomenon 'labor exploitation' is associated with functional dimensions of policy and regulation and its relation to rational action in the economic context. Those case studies of Taiwanese flagship's fishing vessel crew have not yet caught on to the complexity of continuous practice in Indonesian migrants from recruiting procedures to entirely adhering to the causes of migrants' precariousness. Using institutional analysis, the findings show the dynamics between institutions and actors in the labor market, ignoring important micro aspects to transpose to eliminate occupational practices. Neglect of the social-economic context's cognitive element builds a considerable gap between existing beleid and the resulting transformation.